Impact of the kangaroo mother care method on neonatal survival from 2015 to 2020 at the General Reference Hospital in Buta, Democratic Republic of the Congo - KINAMBOLI, Kangoyangala Nicolas; Alworonga , Opara Jean-Pierre; Kafinga, Luzolo Emery (Orapuh Journal, 2024)
IntroductionNeonatal mortality rates remain a significant concern in resource-limited settings, where effective interventions are crucial. The Kangaroo Mother Care (KMC) method has emerged as a promising strategy to improve neonatal survival through skin-to-skin contact and mother-centered care.PurposeThis study aims to assess the impact of the KMC method on neonatal survival and to explore the perceptions of healthcare professionals and mothers regarding this approach at the General Reference Hospital in Buta, Democratic Republic of the Congo.MethodsThis quasi-experimental retrospective study, conducted over a 60-month period (2015–2020) at the General Reference Hospital in Buta, DRC, used a mixed-methods approach to compare neonatal survival rates and complications in preterm and low-birth-weight newborns before and after the introduction of the Kangaroo Mother Care method. Quantitative data were analyzed from 650 preterm newborns, while qualitative experiences and satisfaction levels were gathered from 20 mothers and 15 healthcare professionals.ResultsQuantitative analysis showed a significant increase in neonatal survival rates, rising from 32.6% before the introduction of KMC to 63.4% afterward (p < 0.01). Additionally, the rate of neonatal complications decreased from 26.7% to 8.6% following the method’s implementation. Qualitative findings revealed that 85% of mothers and 90% of healthcare professionals expressed favorable opinions regarding the execution of KMC.ConclusionThe study demonstrates that implementing the Kangaroo Mother Care method at the General Reference Hospital in Buta significantly improved neonatal survival rates, with positive perceptions from both mothers and healthcare professionals. These findings suggest that KMC could be a key strategy for improving neonatal survival in the Democratic Republic of the Congo and similar settings, underscoring the need for continuous training of healthcare staff and the integration of this approach into neonatal health policies.